Impact of Thermal Power Plant Waste Products on Corrosion Dynamics of Pipeline Carbon Steel Alloy in Soil Aqueous Solutions - Camila Porporatti Rosso; Eduardo Ceretta Moreira; Matheus Henrique Baesso; André Gündel; Alexandre Ferreira Galio (Materials Research)
This research examines the effect of thermal power plant desulfurization by-products on pipeline carbon steel alloy corrosion dynamics in soil aqueous solutions to improve soil properties and decrease carbon steel pipeline corrosion rates. Electrochemical tests such as chronopotentiometry, potentiostatic polarization, and electrochemical impedance spectroscopy (EIS) assessed corrosion behavior. Adding desulfurization by-products to soil solutions (DBS) created a transpassive layer during potentiostatic polarization, with a passive current density of about 10μA.cm-2. EIS measurements showed a substantial increase in polarization resistance, with the DBS exhibiting nearly 700 times higher resistance than the standard soil solution (SSS) at 0V (OCP). Raman spectroscopy identified lepidocrocite (γ−FeOOH) in the DBS-treated coupons, while maghemite and akaganeite were found in chloride-enriched conditions.AFM analysis indicated heightened surface roughness with DBS addition, especially with NaCl. XRF and FTIR spectroscopy of the waste products identified them as primarily composed of silica, aluminosilicates, and oxides of calcium, magnesium, and aluminum. The results elucidate DBS's impact on soil corrosion and suggest methods to mitigate corrosion in industrial and environmental contexts. This study enhances the understanding of buried pipeline corrosion mechanisms and presents a new use of thermal power plant waste for corrosion protection.